Les dispositifs d`évaluation des parasportifs pratiquant des sports de petits terrains en fauteuil roulant manuel - Bakatchina, S.; Faupin, A.; Weissland, T. (Movement & Sport Sciences - Science & Motricité, 2021)
The purpose of this narrative literature review was to identify through the internal logics of two collective Paralympic disciplines in manual wheelchairs (MW), the contribution and limits of the main devices accessible to paralympic athletes in MW. As part of performance optimization, paralympic athletes are habitually evaluated in the laboratory or in the field. In laboratory, arm ergometer (AE), wheelchair ergometer (WE) and treadmill (TM) are usually used. AEs do not allow to simulate mechanics gesture of MW propulsion. WEs allow to use the personal MW but, they neutralize rolling resistance of MW casters. TM is more realistic but neutralizes MW steering. Embedded technology is an evolution of laboratory stationary tools. Indeed, instrumented wheel (IW) and inertial measurement unit (IMU) are suitable for measurements in field condition. However, IW weighs limits the behavior of the MW and IMUs do not quantify the forces developed on the handrim. The simulation of the forces exerted on the handrails from the data of the IMUs will allow the development of miniaturized force sensors in perspective.